Screening of Methanolic Plant Extracts against Larvae of Aedes aegypti and Anopheles stephensi in Mysore - Thirumalapura Krishnaiah Mohankumar; Kumuda Sathigal Shivanna; Vijayan Valiakottukal Achuttan (Tehran University of Medical Sciences, 2016)
Background: Mosquitoes transmit serious human diseases, causing millions of death every year. Vector control is facing a threat due to the emergence of resistance to synthetic insecticides. Insecticides of botanical origin may serve as suitable alternative biocontrol techniques in the future. Nine different locally available medicinally important plants suspected to posse larvicidal property were screened against fourth instar larvae of Aedes aegypti and Anopheles stephensi to a series of concentrations of the methanolic extracts. Methods: Susceptibility tests on Ae. aegypti and An. stephensi were conducted using standard WHO methods. The larvae of two mosquito species were exposed to methanolic extracts and mortality counts were made after 24 hours of exposure as per WHO method. Larvae of Ae. aegypti were more susceptible than that of An. stephensi. Results: Among the nine plant species tested, Annona reticulata leaf extract was more effective against Ae. aegypti larvae with LC50 and LC90 values of 95.24 and 262.64 ppm respectively and against An. stephensi larvae 262.71 and 636.94 ppm respectively. The least efficacy was in Cosmos bipinnatus with LC50 and LC90 values of 442.6 and 1225.93 ppm against Ae. aegypti and LC50 and LC90 values of 840.69 and 1334.01 ppm of Thespesia populnea against An. stephensi. Conclusion: The crude methanolic extract of the An. reticulata with good larvicidal efficacy could be considered for further characterization to control mosquito vectors instead of chemical insecticides. High efficacy found in An. reticulata extract will be considered for further studies to isolate the bioactive compound.